Agricultural commercialization and asset growth for poverty reduction: Evidence from panel data for rural Vietnam - Oliver Schulte; Julian Mumber; Trung Thanh Nguyen (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2023)
Poverty remains a substantial threat in rural areas of many developing countries, and solving this problem requires an in-depth understanding of the income generating capacity that determines poverty. This paper examines the impact of agricultural commercialization on the capability of rural households to accumulate assets and on structural and multidimensional poverty. A longitudinal dataset of around 2000 households with a total of 9781 observations from five rural surveys undertaken in the period 2008 - 2017 in Vietnam is used. Results from a fixed effects regression with an instrumental variable and a control function approach show that agricultural commercialization has a positive effect on the accumulation of assets and reduces multidimensional and structural poverty over time. However, the effect is not homogeneous and larger for households not mainly engaged in rice commercialization. This suggests that commercialization can be a path out of poverty, especially if policy makers move towards utilizing other crops instead of rice.
Keywords: C21; I32; Q12; Q13; 330; Asset growth; Asset-based income; Commercialization; Fixed effects; Instrumental variable; Control function